The A to Z of Taoism - Pas, Julian F.; Pas, Julian F. (Lanham, Md. : Scarecrow Press, 2006)
"As the least known of China's "Three Teachings" - the others being Buddhism and Confucianism - Taoism serves as a supplement and a corrective, as it has often done in the past. For this reason, it is enjoying ever greater appreciation around the world, especially in the West. Implicit and intuitive, the "Way" cannot be explained directly, but it can be intimated - as is done in this book." "The A to Z of Taoism starts with a detailed chronology of Taoism and its relationship to both China and other teachings, while the introduction expands on these ideas. The dictionary contains several hundred entries and provides a more detailed treatment of significant people, gods and demons, concepts, practices, rituals, scriptures, and schools. A comprehensive bibliography suggests further reading."--BOOK JACKET.
"The A to Z of Taoism is a revised paperback edition of the Historical Dictionary of Taoism, by Julian F. ... 1998"--title page verso.
Includes bibliographical references (pages 377-412).
Description based on print version record.
Keywords: Taoism -- History -- Dictionaries; Taoïsme.; BODY, MIND & SPIRIT / Spirituality / Paganism & Neo-Paganism; RELIGION / Comparative Religion; Electronic books